Open In App

Arithmetic Series

Last Updated : 04 Sep, 2023
Like Article

An ordered list of numbers is called a To findsequence. Each number in the sequence is called a term. The sequence usually has patterns that allow us to predict what the next term of the sequence will be. An arithmetic series is the sum of sequences in which each term is computed from the previous one by adding and subtracting a constant. Or we can say that an arithmetic progression can be defined as a sequence of numbers in which for every pair of consecutive terms, the second number is found by adding a constant number to the previous one. ,

In Arithmetic Series/Progression we come across three terms which are: 

  • Common difference(d)
  • nth term(an)
  • Sum of the first n terms(Sn)

Here, all the above three terms represent the property of the arithmetic progression. 

To find the common difference in the arithmetic progression the following procedure is followed: 

 d = a2 – a1 = a3 – a2 = a4 – a3….. = an-an-1


  • a1, a2, a3….an  are the terms of the series
  • “d” is the common difference which can be positive, negative or zero

    Also, an arithmetic progression can also be written in the form of common difference as shown below: 

a, a + d, a + 2d, a + 3d, a + 4d, ………. , a + (n – 1)d

Where, “a” is the first term of series. 

There are two major formulas while reading arithmetic progression: 

  • nth term of Arithmetic Series 
  • Sum of first n Terms 

nth term of Arithmetic Series

The formula for nth term is,

an = a + (n−1)d


  • a is the first term
  • d is the common difference
  • n is the number of terms
  • an is the nth term

Sum of First n Terms

The sum of first “n” terms of the series can be easily found is we know the first term of the series and total terms. The formula for finding the sum of first “n” terms is: 

Sn = n/2 [2a + (n−1)d]


  • a is the first term 
  • d is the common difference 
  • n is the number of terms.

Arithmetic Series Sigma Notation

Sigma notation looks like the below: 

ΣFn=i [expression]

Here in the above expression the ‘i’ describes the initial value. The ‘f’ describes the final value and the expression refers for the function and the ‘E’ symbol is the Greek symbol called sigma. 

For Example: Σ10n=1 (3n+7) 

Here the value of n starts with ‘1’ and ends at ’10’. When we start putting the value of n we get the arithmetic series just like below:

10 + 13 + 16 + 19……+ 37

Now for sigma notation, there is the formula used to find the sum of arithmetic series given above 

Sn = n/2(a1 + an)

Here ‘n’ is the number of terms in the series and a1 and an is the first and last term of the series respectively. 
For the above example we get the following values: 

  • n = 10 
  • a1 = 10 
  • an = 37 

Putting the value in the above equation 

Sn = 10(10+37)/2 = 235


Σ10n=1 (3n+7) = 235 

Arithmetic Series Sum Expression

When we get the arithmetic series expression like below: 

1 + 5 + 9 +……+ 45 

Now here we know that the expression for summation is as follows: 

Sn = n/2(a1 + an)

Here we know the value 

  • a1 = 1
  • an = 45
  • d = (5-1) = 4

We don’t know the value of ‘n’ so we’ll find it using the below method: 

n = (an – a1)/d + 1 = (45 – 1)/4 + 1 = 12

Therefore, the value of the n is 12.

Counting the sum of the series goes as Sn = n/2(a1 + an)

Sn = 12(1 + 45)/2 = 276

Arithmetic Series Recursive Formula

Recursive Formula gives to two information:

  • First term of the sequence 
  • Pattern rule to find any term from the term that comes before it 

Suppose, we have the series 3, 5, 7….. then here the first term of the series is a1 = 3 Now, from above the series we see that the formula for an Will be as below: 

If a1 = 3 than an = a(n-1) + 2

Therefore, we have to add ‘2’ to the previous term to get to next term of the series. Hence, finding the rest of the term below: 

  • a1 = 3
  • a2 = a1+2 = 3 + 2 = 5
  • a3 = a2 + 2 = 5 + 2 = 7
  • a4 = a3 + 2 = 7 + 2 = 9
  • a5 = a4 + 2 = 11… and so on

Proof of Finite Arithmetic Series Formula

As we know that,

Sn = n/2(a1 + an)

As we know at Sn  is the sum of the arithmetic series of ‘n’ terms, therefore, we can display it like below: 

Sn = 1 + 2 + 3….+ (n-1) + n

Sn = n + (n-1) +…+ 3 + 2 + 1 

Adding both the Sn series we get the following result: 

 2Sn = n+1 + 2+(n-1) + 3+(n-2)…..

2Sn = n(n+1)

Sn = n(n+1)/2

In the above formula, we find that sum of every term on the left-side turn out to be ‘n+1’ for ‘n’ times. 
Hence, we have proved,

Sn = n(n+1)/2 

Like Article
Suggest improvement
Share your thoughts in the comments

Similar Reads